RETRACTED: Selective reflection study of excitation-dependent dipole-dipole interaction in dense rubidium vapour - Bobrov Andrei; Sautenkov Vladimir; Saakyan Sergey; Zelener Boris (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001